Fasting Serum Magnesium Level and its Association with Type 2 Diabetes Mellitus and its Chronic Complications - Lamsal, Manoj; Thapaliya, Sabin; Thapa, Pradeep; Bhandari , Roshan; Sangroula, Raj K; Sayami, Matina; Shrestha, Pradeep K (Journal of Institute of Medicine Nepal, 2021)
Introduction Diabetes mellitus is one of the most common metabolic disorders. Hypomagnesaemia is a common feature in patients with type 2 diabetes mellitus (T2DM). This study aims to assess the serum magnesium level and its association with chronic complications in patients with T2DM. Methods A total of 173 T2DM patients at Tribhuvan University Teaching Hospital were evaluated from July 2016 to August 2017. Patients were investigated for fasting serum magnesium level, fasting plasma glucose (FPG), postprandial plasma glucose (PPG), Glycosylated haemoglobin (HbA1c) and also target organ evaluation for diabetes. Data was analyzed using SPSS version 20. Results Hypomagnesaemia was found in 86 patients out of the 173 enrolled patients. Observations revealed significant association between hypomagnesaemia and various microvascular complications viz. retinopathy (p=0.001), neuropathy (p<0.001) and nephropathy (p<0.001). There was also a significant association between hypomagnesaemia and FPG (p=0.008) and HbA1c (p=0.009). The overall prevalence of hypomagnesaemia among T2DM patients was 49.7% and the prevalence of hypomagnesaemia was significantly higher (74%) among diabetic patients with microvascular complications (p=0.001) compared to diabetics with no microvascular complications. Conclusion This study showed a high prevalence of hypomagnesaemia among T2DM patients. A significant association was seen between hypomagnesaemia and various microvascular complications like retinopathy, neuropathy and nephropathy. Routine surveillance and timely treatment of hypomagnesaemia is advisable for patients with T2DM.